CATALIST PERFORMANCE OF SYNTETIC ZEOLITE ZSM-5 â Al2O3 IN CRACKING REACTION OF PALM OIL TO BECOME GASOLINE FRACTION OF HYDROCARBON - Setiadi Setiadi; Benny A. W. (Institut Teknologi Bandung, 2006)
The requirement of fuel increases without balancing with its production causing the oil resources from fuel will immediately finished. Therefore, palm oil as renewable energy resources is selected for fuel production especially gasoline. Catalitic cracking process by using ZSM-5/Alumina catalys is selected in this research. The reaction was conducted in a simple fixed bed reactor with the pressure of 1.5 atm during half hour and WHSV 1,8 h-1 dan 2,4 h-1. The reaction result product then analyzed by using GC-FID for identify the gasoline fraction obtained, and FT-IR for identify the bonding kind of the samples. The baits used were pure palm oil, oxydized oil,POME (Palm Oil Methyl Esther), and oil with methanol. The parameters of the research were temperature (350 â 500 °C), catalist composition (5 - 20 %), and kinds of baits. The results showed that the composition of catalist 5% at reaction temperature of 400 °C with the bait of POME resulting the highest gasoline yield of 63,1%.